Attitudes towards migrants and preferences for asylum and refugee policies before and during Russian invasion of Ukraine: The case of Slovakia - Magdalena Adamus; Matúš Grežo (Masaryk University, Faculty of Economics and Administration, 2023)
Extant literature shows that well-being is one of the key drivers of attitudes towards migrants as well as preferences for asylum and refugee policies. To investigate the underpinnings of these relationships, two studies on representative samples of 600 Slovaks each were conducted before the Russian invasion of Ukraine and during its initial phase. The results show that well- being had a stable positive relationship with attitudes towards migrants across the studies, albeit not with preferences for asylum and refugee policies. During the Russian invasion of Ukraine, the negative feelings elicited by the war predicted preferences for asylum and refugee policies beyond well-being. The divergence between the attitudes towards migrants and the preferences urges that there is a need to extend the traditional focus on general attitudes towards migrants. Finally, the results indicate that incorporating psychological factors, such as well-being and emotional responses to the looming threat of war, may considerably inform the debate surrounding the support for inclusive asylum and refugee policies.
Keywords: D64; F22; I31; K37; 330; well-being; attitudes towards migrants; asylum and refugee policies; migration crisis; common ingroup identity model